Do interventions to promote walking in groups increase physical activity? A meta-analysis - Kassavou Aikaterini; Turner Andrew; French David P (BMC, 2013)
Abstract Objective Walking groups are increasingly being set up but little is known about their efficacy in promoting physical activity. The present study aims to assess the efficacy of interventions to promote walking in groups to promoting physical activity within adults, and to explore potential moderators of this efficacy. Method Systematic literature review searches were conducted using multiple databases. A random effect model was used for the meta-analysis, with sensitivity analysis. Results The effect of the interventions (19 studies, 4 572 participants) on physical activity was of medium size (d = 0.52), statistically significant (95%CI 0.32 to 0.71, p < 0.0001), and with large fail-safe of N = 753. Moderator analyses showed that lower quality studies had larger effect sizes than higher quality studies, studies reporting outcomes over six months had larger effect sizes than studies reporting outcomes up to six months, studies that targeted both genders had higher effect sizes than studies that targeted only women, studies that targeted older adults had larger effect sizes than studies that targeted younger adults. No significant differences were found between studies delivered by professionals and those delivered by lay people. Conclusion Interventions to promote walking in groups are efficacious at increasing physical activity. Despite low homogeneity of results, and limitations (e.g. small number of studies using objective measures of physical activity, publication bias), which might have influence the findings, the large fail-safe N suggests these findings are robust. Possible explanations for heterogeneity between studies are discussed, and the need for more investigation of this is highlighted.